Age Differences in Adaptive Decision Making: The Role of Numeracy - Chen, Yiwei (Educ Gerontol, 2014)
The primary purposes of the present study were to examine age differences in adaptive decision making and to evaluate the role of numeracy in mediating the relationship between age and adaptive decision making. Adaptive decision making was assessed by the Cups task (Levin, Weller, Pederson, & Harshman, 2007). Forty-six younger (18 to 24 years old) and 37 older adults (61 to 89 years old) completed the Cups task. In addition, the Numeracy Scale (Lipkus, Samsa, & Rimer, 2001) was used to measure individual numeric ability. Adaptive decision making was operationalized by the Expected Value sensitivity (i.e., the product of probability and outcome magnitudes) across the gain and the loss domains. Older adults had significantly lower Expected Value sensitivity than young adults. In addition, older adults demonstrated significantly lower numeracy than younger adults. Finally, numeracy partially mediated the relationship between age and adaptive decision making. It is suggested that older adults’ declined decision making may be partially due to their declined numeric abilities. Implications were discussed in numeracy education and public policies concerning older adults.